Implementation of Literature Learning to Enhance Students’ Appreciation at SMP Negeri 4 Panca Rijang - Jusrianto Jala; Sam Hermansyah; Handy Ferdiansyah; Suhartini Khalik; Usman M (Universitas Muhammadiyah Enrekang, 2025)
This study aims to analyze the implementation of literature learning in enhancing students’ literary appreciation at SMP Negeri 4 Panca Rijang. The research involved a sample of 30 eighth-grade students selected through purposive sampling. A descriptive qualitative design was employed to examine how literature learning strategies—such as reading activities, guided discussions, and appreciation tasks—contributed to students’ understanding and emotional engagement with literary texts. Data were collected through classroom observations, student worksheets, and interviews, then analyzed through thematic coding. The findings indicate that the use of interactive literature learning methods significantly supports students’ ability to identify intrinsic elements, interpret meanings, and express personal responses to stories and poems. Furthermore, students demonstrated increased motivation and confidence in appreciating literary works after the implementation of structured learning steps. The study concludes that literature learning, when systematically planned and delivered, can effectively improve students’ literary appreciation at the junior secondary school level